Staphylococcus aureus toxin LukSF dissociates from its membrane receptor target to enable renewed ligand sequestration. Issue 3 (3rd December 2018) - Haapasalo, Karita; Wollman, Adam J. M.; de Haas, Carla J. C.; van Kessel, Kok P. M.; van Strijp, Jos A. G.; Leake, Mark C.
ABSTRACT: Staphylococcus aureus Panton‐Valentine leukocidin is a pore‐forming toxin targeting the human C5a receptor (hC5aR), enabling this pathogen to battle the immune response by destroying phagocytes through targeted lysis. The mechanisms that contribute to rapid cell lysis are largely unexplored. Here, we show that cell lysis may be enabled by a process of toxins targeting receptor clusters and present indirect evidence for receptor "recycling" that allows multiple toxin pores to be formed close together. With the use of live cell single‐molecule super‐resolution imaging, Förster resonance energy transfer and nanoscale total internal reflection fluorescence colocalization microscopy, we visualized toxin pore formation in the presence of its natural docking ligand. We demonstrate disassociation of hC5aR from toxin complexes and simultaneous binding of new ligands. This effect may free mobile receptors to amplify hyperinflammatory reactions in early stages of microbial infections and have implications for several other similar bicomponent toxins and the design of new antibiotics.—Haapasalo, K., Wollman, A. J. M., de Haas, C. J. C., van Kessel, K. P. M., van Strijp, J. A. G., Leake, M. C. Staphylococcus aureus toxin LukSF dissociates from its membrane receptor target to enable renewed ligand sequestration. FASEB J. 33, 3807–3824 (2019). www.fasebj.org